Hubungan antara Kelahiran Asfiksia dengan Perkembangan Balita - Mulidah, Siti; Haryati, Welas; Fitriyani, Aris (Jurnal Keperawatan Soedirman, 2006)
Asphyxia that occur in period of neonatal can cause the damage baby organs and it also can cause the damage of brain for the severe cases. This situation can cause developmental disorder of the baby language, social, and motorist in the future. So early monitoring of the growth and development of under five years children are very important to find problems or disorder, there for anticipated treatment can be done. This study aim to prove the correlation of asphyxia baby delivery and the developmental of under five years children. This study utilized an observational method by case control design. The respondent was under five years children who came to children poly clinic of Prof. Dr. Margono Soekarjo hospital in period of 1 June to 31 July 2006. The respondents were appropriated with inclusion and exclusion criterion. The number of respondents was 60 ( case group = 30 and control group = 30). The univariate analysis showed the development of motorist, social, and language under five years children of asphyxia baby delivery showed 50 percent hard motorist were normal and 50 percent were found disturbance. On the other hand, the development of soft motorist showed 16,7 percent were found disturbance and 83,3 percent were normal. The development of social showed 20,0 percent were found disturbance and 80,0 percent were normal. For the language developmental was found 71,7 percent normal and 28,3 percent were found disturbance. The development of under five years children without asphyxia was normal for all of them. Bivariate analysis showed the correlation of asphyxia baby delivery and the development under five years children was significance statistically ( p = 0,02; OR = 3,5 ; CI 95 percent = 1,96 – 31,68). The correlation of asphyxia baby delivery and the developmental of under five years children was significant statistically, and asphyxia baby delivery increased the risk of developmental disturbance of under five years children.